2009
DOI: 10.1007/s10531-009-9677-4
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of wind farms on birds? A case study in southern Spain

Abstract: Wind farming is a relatively new form of obtaining energy that does not cause air pollution or other forms of environmental degradation associated with fossil fuel technologies. However, their use impacts on the environment, and the current rate at which they are being put into operation, combined with poor understanding of their medium-and long-term impact, is a cause of concern. Wind farms represent a new source of impact and disturbance for birds that adds to the long list of disturbance factors caused by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
1
28
3
Order By: Relevance
“…This may have been especially true for the ferruginous hawks in our study because this species increases defense behavior (Keeley and Bechard ) and flushes at greater distances with consecutive disturbances near the nest, suggesting they may be particularly sensitive to operations and maintenance activities (White and Thurow , Keeley and Bechard ). Repeated exposure to such stimuli can alter flight trajectories or disrupt foraging and nesting behaviors, ultimately leading to changes in habitat use within the home range relative to the spatial configuration of nearby turbines or operational activities (Farfán et al , Pearce‐Higgins et al , May 2015). The extent of such displacement would depend upon the perceived risk of mortality while foraging and flying near turbines versus the availability of suitable alternative habitats nearby (May ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have been especially true for the ferruginous hawks in our study because this species increases defense behavior (Keeley and Bechard ) and flushes at greater distances with consecutive disturbances near the nest, suggesting they may be particularly sensitive to operations and maintenance activities (White and Thurow , Keeley and Bechard ). Repeated exposure to such stimuli can alter flight trajectories or disrupt foraging and nesting behaviors, ultimately leading to changes in habitat use within the home range relative to the spatial configuration of nearby turbines or operational activities (Farfán et al , Pearce‐Higgins et al , May 2015). The extent of such displacement would depend upon the perceived risk of mortality while foraging and flying near turbines versus the availability of suitable alternative habitats nearby (May ).…”
Section: Discussionmentioning
confidence: 99%
“…Breeding raptors exposed to other types of anthropogenic activity alter their spatial use of the landscape and make extra‐home range movements (Andersen et al ), or abandon nests altogether (White and Thurow ). Many studies have reported that displacement and disturbance effects from wind energy development occurring at a variety of spatial scales, from vacancy of nesting areas to changes in movement patterns and turbine avoidance within the home range, are negligible (Madders and Whitfield , Hernández‐Pliego et al ) or inconclusive for some raptors (Drewitt and Langston ); however, other studies report they suspected displacement by wind energy development as the primary reason for decreased abundance (Farfán et al , Pearce‐Higgins et al , Garvin et al , Dahl et al ). These inconsistencies likely vary depending upon the extent of development and species‐specific tolerance to disturbance (May ).…”
mentioning
confidence: 99%
“…Despite the potential negative effects of wind farms on birds and bats (e.g. Langston and Pullan 2003;Barrios and Rodríguez 2004;Drewitt and Langston 2006; but see Farfán et al 2009;review in Stewart et al 2007), we are currently undergoing a period of expansion of wind farm energy in Spain, with undetermined consequences over resident and migrant species (Tellería 2009a, b, c). Problems arise when the effects of several threats are combined, including the exposure to poison and veterinary drugs, added to an increase in mortality due to the installation of wind farms close to breeding or feeding areas, as it is happening in some Spanish regions.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe in general but particularly in Spain, there has been an unprecedented increase of wind farms, and many more are projected (Desholm 2006;Stewart et al 2007;de Lucas et al 2007;Atienza et al 2008;Tellería 2009a;Carrete et al 2009;Farfán et al 2009). …”
Section: Introductionmentioning
confidence: 99%